Adolescence : - Cobb, Nancy J. (McGraw-Hill, 2004)
This text provides a comprehensive survey of the research findings and theories of adolescent development, and shows how this information can be applied to help adolescents meet the challenges they face as they grow into adulthood. Developmental implications of ethnic, cultural, and socioeconomic differences are integrated into every chapter, and similarities and differences between early and late adolescent development are discussed throughout the text.